Application of Project Based Learning Model by Using Flipbook Media to Improve the Narrative Text Writing Skill - Lestari, Hadi; Cahyono, Bambang Eko Hari; Huda, Muhammad Binur (International Journal of Essential Competencies in Education, 2025)
The research aims to get a clear description about the application of Project Based Learning Model by using Flipbook media to improve the narrative text writing skill at the fifth grade students of SDN 4 Margopatut. The research used a classroom action research method with the type of participant research. The informants in this study were the school principal, grade fifth teacher, and grade fifth students. Events in this research were all forms of learning activities in the classroom. The documents of this research were lesson plans, syllabus, and score list. The data collection techniques used was interviews, observations, narrative text writing tests, and documentation. The data collection instruments in this research were interview instruments, observation sheets, and assessment sheets for narrative text writing skills. The results showed that the application of learning to write narrative text by applying the Project Based Learning model with Flipbook media to fifth grade students of SDN 4 Margopatut have improved, both the learning process and the results of writing narrative text. The improvement of the learning process can be seen from the increasing value of student attitudes in learning each cycle. The average score of students before the study was 69. In Cycle I, the average student score increased by 7% to 74. In Cycle II, the students' average score increased by 8% to 80. 11 out of 13 or 85% fifth grade students of SDN 4 Margopatut, got score above the minimum completeness criteria.